Effect of graphene on microstructure and mechanical properties of cast AZ91 alloy - WANG Dianjun; LIANG Ying (Journal of Aeronautical Materials)
Grain refinement plays an important role to enhance the mechanical properties of magnesium alloys. In this work，graphene-reinforced AZ91 composites were successfully prepared by pre-dispersion combined with gravity casting method. The microstructure of the GNP/AZ91 composites was characterized using OM，SEM，TEM，etc. The results show that the grain size of AZ91 alloy gradually decreases with the increase of GNP content. When 1% GNP is added， the grain size of AZ91 alloy is reduced from 415 μm to 86 μm，with the refinement efficiency of 79%. It is found and revealed through TEM observation that the refining mechanism of GNP on AZ91 alloy is mainly Al4C3 phase obtained by in-situ reaction of GNP with Al element in AZ91 melt， which can promote the heterogeneous nucleation of α-Mg grains， thus achieving significant grain refinement effect. When the GNP content is increased to 0.5%， the best mechanical properties are obtained for AZ91 alloy with the UTS， YS and EL reaching 150， 96 MPa and 2.1%，the improvement of 34%， 32% and 91% respectively compared to AZ91 alloy.